Recommendation Systems: Different Techniques, Challenges and Future Directions (International Journal of Innovative Research in Engineering & Management, 2021)
As a significant research focus, the Recommender Systems  (RS) has developed to assist customers find goods online by  providing suggestions that closely match their interest. This  article provides a review of achievements and the future  direction in the area of Recommended Systems. It was  believed that helping users deal with the problem of data  overload was the original purpose of information retrieval  systems or search engines, but what differentiates proposed  solutions from the current search engines is the needs of  customized helpful and entertaining. The "intelligence"  element is what makes a proposal more intriguing and helpful.  Intelligence is one of the major ways of customization to  know the interests of the user, predict the unknown  preferences of the user, and ultimately offer recommendations  by matching the query and the material beyond a simple  search. This study has resulted in many significant findings,  which will enable present and the future generation  researchers of RS to assess and define the roadmap of their  research in this area.
Keywords: Challenges; Feedback; Filtering techniques; Future direction; Issues; Research trends; Recommendation Systems